Correlation between Total Phenolic Content and Antibacterial Activities of Some Selected Traditional Plants against Some Species of Pathogenic Bacteria - Abuga, Ibrahim; Sulaiman, Shaida Fariza; Sani, Ibrahim; Jiga, Sufiyanu Abubakar; Aliero, Adamu Almustapha; Muhammad, Amina (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Plants produce non-nutritive compounds known as secondary metabolites. These compounds can be found in several parts of the plants. Emphases have been placed on these compounds as curative agents in treating different types of diseases. Total phenolic contents of the plant extracts (leaf extract of Anacardium occidentalle, bulb extract of Allium sativum, bark extract of Casaurina equisetifolia, leaf extract of Dysophylla auriculata and bark extract of Mimusops elengi) were determined by using Folin-Ciocalteu method, and the values were expressed in microgram (µg) gallic acid equivalent (GAE) to 1 milligram (mg) of extract. The antibacterial activities of the 80% methanolic extracts of the plants were determined against nine species of pathogenic bacteria; that were Escherichia coli 0157:H7, Vibrio alginolyticus (ATCC 17749), Vibrio parahaemolyticus (ATCC 17082), Salmonella paratyphi (ATCC 9150), Yersiniae enterocolitica (ATCC 23715), Listeria monocytogenes (ATCC 19115), Salmonella typhi (ATCC 14028), Escherichia coli (ATCC 0157) and Staphylococcus aureus (ATCC 700699). Out of the five selected samples, the highest phenolic content was recorded with the bark extract of Mimusops elengi (442.59 ± 2.09). From the antibacterial screening, the most potent extract was observed with the bark extract of Mimusops elengi against L. monocytogenes (ATCC 19115), with a minimum inhibitory concentration value of 15.63 µg/mL, then followed by Allium sativum with 62.5 µg/mL. The correlation determined in this study between the total phenolic content and the antibacterial activity of the bark extract of Mimusops elengi confirmed its effectiveness against the screened species of bacteria. This work may be useful for the pharmaceutical industry in developing new natural product-based therapy for pathogenic bacteria.